Khwāmmaipentham læ khwāmkhatyǣng : phǣndin dīeokan tǣ samư̄an yū khon la lōk : rāingān sarup prachum Kānprachum thāng Wichākān Sangkhomwitthayā Phūmiphāk Phāk ʻĪsān, Wansao thī 4 Kanyāyon 2553 na Rōngrǣm Phūnmǣn Rāchā ʻŌ̜khit, Čhangwat Khō̜n Kǣn - Chainarong Sētchư̄a (Khana Manutsayasāt læ Sangkhommasāt, Mahāwitthayālai Khō̜n Kǣn, 2010)
Conference papers on social justice, social development, and political conflicts in Thailand.